2022
DOI: 10.1186/s13756-022-01056-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nosocomial SARS-CoV-2 infections in patients: results from a retrospective matched case–control study in a tertiary care university center

Abstract: Background Factors contributing to the spread of SARS-CoV-2 outside the acute care hospital setting have been described in detail. However, data concerning risk factors for nosocomial SARS-CoV-2 infections in hospitalized patients remain scarce. To close this research gap and inform targeted measures for the prevention of nosocomial SARS-CoV-2 infections, we analyzed nosocomial SARS-CoV-2 cases in our hospital during a defined time period. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Nosocomial coronavirus disease 2019 (COVID-19) outbreaks are associated with a poor patient prognosis, as well as disruption of medical services due to staff shortages. 1 Because inpatients frequently have co-morbidities or are immunocompromised, they are susceptible to severe COVID-19 infection. Thus, to prevent nosocomial outbreaks of COVID-19, many hospitals use multi-layered preventive strategies such as universal masking, universal reverse transcription polymerase chain reaction testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), screening of patients, resident caregivers, and healthcare workers (HCWs)’ symptoms and epidemiologic links, and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial coronavirus disease 2019 (COVID-19) outbreaks are associated with a poor patient prognosis, as well as disruption of medical services due to staff shortages. 1 Because inpatients frequently have co-morbidities or are immunocompromised, they are susceptible to severe COVID-19 infection. Thus, to prevent nosocomial outbreaks of COVID-19, many hospitals use multi-layered preventive strategies such as universal masking, universal reverse transcription polymerase chain reaction testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), screening of patients, resident caregivers, and healthcare workers (HCWs)’ symptoms and epidemiologic links, and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective cohort study found in a crude analysis of 122 patients across three outbreak wards that being exposed to a symptomatic COVID-19 patient within the same 4-bed bay regardless of proximity in the room was associated with doubling the risk of becoming a case (crude RR, 2.3, 95% CI 1.42–3.65) [ 27 ]. In a matched case–control by Aghdassi et al [ 28 ], the multivariate analysis revealed that presence on a ward that experienced a COVID-19 outbreak (aOR 15.9, 95% CI 2.5–100.8) and documented contact with a COVID-19 case (aOR 23.4, 95% CI 4.6–117.7) to be the primary factors for nosocomial COVID-19 infections in patients [ 28 ]. This latter study and the results of our outbreak investigation supports the need to preemptively isolate patients known to be exposed to cases.…”
Section: Discussionmentioning
confidence: 99%
“…A national study from India had 21 (1.43%) neonates who tested positive beyond 72 h and reported these as horizontal transmission and had a higher positivity rate in neonates rooming in with their mothers ( 22 ). Being in a ward where there is a documented SARS-CoV-2 outbreak and documented contact with a suspected SARS-CoV-2 patient have been reported as risk factors for nosocomial SARS-CoV-2 infections ( 37 ). The rates of infection were also noted to be higher if the duration of exposure was for longer than 5 days ( 4 ).…”
Section: Discussionmentioning
confidence: 99%